Spino cranial angle as a predictor of loss of cervical lordosis after laminoplasty in patients with cervical myelopathy - Zheng Wang (BMC Surgery, 2021)
Abstract Background To explore the relationship between spino cranial angle (SCA) and loss of cervical lordosis (LOCL), and to determine whether SCA has the ability to predict LOCL for patients with cervical myelopathy. Methods A total of 68 consecutive patients with cervical myelopathy who received laminoplasty (LAMP) were selected to the current study. C2–C7 lordosis was defined as a representation of the cervical alignment. Alignment change > 0° was considered LOCL. Multiple linear regression analysis was applied to evaluate the association between LOCL and various sagittal parameters at preoperative, such as SCA, CL, T1s and cSVA. Linear regression analysis was applied to evaluate the relationships between LOCL and preoperative SCA in each subgroup. Results Patients were assigned to three groups depending on the quartile of preoperative SCA. The first quarter of patients were defined as the low SCA group, the last quarter were defined as the high SCA group and the middle half were defined as the middle SCA group. There was no statistically significant difference in age, sex and the type of OPLL among the three groups. Patients in the low SCA group showed more cervical lordosis before surgery and more LOCL after LAMP (p < 0.001). After linear regression analysis for SCA and LOCL, preoperative SCA was negatively correlated with LOCL in the low SCA group (r = − 0.857, p < 0.001) and high SCA group (r = − 0.515, p = 0.034). However, there was no significant correlation between preoperative SCA and LOCL in the middle SCA group (r = 0.027, p = 0.881). Conclusions Patients with lower SCA had more lordosis preoperatively and performed more LOCL after LAMP at 2 years of follow-up. Both too high or low preoperative SCA were negatively correlated with the degree of LOCL, while when the SCA fluctuates in a suitable range, it is easier to compensate for the changes of cervical sagittal alignment.